JAK-STAT pathway, type I/II cytokines, and new potential therapeutic strategy for autoimmune bullous diseases: update on pemphigus vulgaris and bullous pemphigoid - Xiaoying Lin; Xiang Li; Zhifang Zhai; Mingwang Zhang (Frontiers in Immunology)
Autoimmune Bullous Diseases (AIBDs), characterized by the formation of blisters due to autoantibodies targeting structural proteins, pose significant therapeutic challenges. Current treatments, often involving glucocorticoids or traditional immunosuppressants, are limited by their non-specificity and side effects. Cytokines play a pivotal role in AIBDs pathogenesis by driving inflammation and immune responses. The JAK-STAT pathway is central to the biological effects of various type I and II cytokines, making it an attractive therapeutic target. Preliminary reports suggest that JAK inhibitors may be a promising approach in PV and BP, but further clinical validation is required. In AIBDs, particularly bullous pemphigoid (BP) and pemphigus vulgaris (PV), JAK inhibitors have shown promise in modulating pathogenic cytokine signaling. However, the safety and selectivity of JAK inhibitors remain critical considerations, with the potential for adverse effects and the need for tailored treatment strategies. This review explores the role of cytokines and the JAK-STAT pathway in BP and PV, evaluating the therapeutic potential and challenges associated with JAK inhibitors in managing these complex disorders.